2006
DOI: 10.1111/j.1365-2249.2006.03155.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of neutrophils in the murine model of haemolytic uraemic syndrome: mechanisms involved in Shiga toxin type 2-induced neutrophilia

Abstract: SummaryIt has been demonstrated that infections due to Shiga toxins (Stx) producing Escherichia coli are the main cause of the haemolytic uraemic syndrome (HUS). However, the contribution of the inflammatory response in the pathogenesis of the disease has also been well established. Neutrophils (PMN) represent a central component of inflammation during infections, and patients with high peripheral PMN counts at presentation have a poor prognosis. The mouse model of HUS, by intravenous injection of pure Stx typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…A few studies showed that there were consistent vascular or glomerular lesions (12,16,48), and the descriptions of these lesions varied between studies, confirming our findings that glomerular disease is present but mild in EHEC-infected mice. Several studies that used an injection model, in which Stx or Stx in combination with lipopolysaccharide was injected parenterally into mice, described glomerular lesions (11,13,15,20,45), supporting our finding that virulent EHEC is capable of inducing glomerular disease in mice.…”
Section: %)supporting
confidence: 74%
See 1 more Smart Citation
“…A few studies showed that there were consistent vascular or glomerular lesions (12,16,48), and the descriptions of these lesions varied between studies, confirming our findings that glomerular disease is present but mild in EHEC-infected mice. Several studies that used an injection model, in which Stx or Stx in combination with lipopolysaccharide was injected parenterally into mice, described glomerular lesions (11,13,15,20,45), supporting our finding that virulent EHEC is capable of inducing glomerular disease in mice.…”
Section: %)supporting
confidence: 74%
“…Donohue-Rolf et al (10) showed that isogenic Stx2-negative mutants failed to cause neurologic lesions or signs in gnotobiotic piglets, but renal lesions were not described. Finally, several studies have demonstrated the nephrotoxic effect of parenterally injected Stx1 or Stx2 (11,13,15,20,25,45,51), again providing indirect evidence that Stx is at least partially responsible for renal disease.…”
Section: %)mentioning
confidence: 99%
“…Neutrophils are activated during HUS (10), resulting in the release of factors capable of causing tissue damage. Furthermore, recent studies of a murine model of disease suggest that Stx2-induced lethality and renal damage are reduced in neutrophil-depleted mice (8). However, there have been conflicting reports regarding whether Stx directly promotes neutrophil activation or whether Stx indirectly promotes neutrophil activation by inducing an inflammatory response in other cells.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the neutrophils of HUS patients were shown to induce endothelial injury in vitro (10). Recent studies have shown that neutrophil depletion in mice results in a reduction in Stx2-induced lethality and renal damage (8).…”
mentioning
confidence: 99%
“…Peripheral blood PMNs were isolated from pooled heparinized murine blood taken from tail veins of WT or ⌬␣ M mice, both males and females, by centrifugation through Ficoll-Hypaque, followed by 6% dextran sedimentation; the contaminating erythrocytes were removed by hypotonic lysis (102). The cells obtained by this technique were Ͼ90% PMNs (21,33,106). For each experiment, PMNs from five to seven mice were pooled.…”
Section: Methodsmentioning
confidence: 99%